Minimal Information Structural Realism - Krzanowski, Roman (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2017)
This paper presents Minimal Information Structural Realism (MISR), that claims that information (signified by I) is an ontologically and epistemologically objective entity (signified by R) and is apprehended as, but not identical to structures perceived in nature (signified by S). Two informal arguments are presented in support of this claim. One argument is based on the conclusions from models of quantum mechanics (QM) and cosmology, while the other argument is referred to as incompleteness of epistemic definitions of information. MISR is not associated directly with the structural realism (SR) of the ontic or epistemic kinds, and is only remotely related to the concept of information structural realism (ISR) defined by Floridi.
Keywords: information; information ontology; structure; structural realism; information structural realism